Everyday ethics : moral theology and the practices of ordinary life - Lamb, Michael, 1982-; Williams, Brian A., (Brian Alan), 1971- (Georgetown University Press, 2019)
What might we learn if the study of ethics focused less on hard cases and more on the practices of everyday life? In Everyday Ethics, Michael Lamb and Brian Williams gathered some of the world's leading scholars and practitioners of moral theology (including some Georgetown University Press authors) to explore that question in dialogue with anthropology and the social sciences. In a field largely begun by Michael Banner, contributors engage with and extend his ideas of ethics as it is practiced in daily life. Crossing disciplinary boundaries, these scholars analyze the ethics of ordinary practices--from eating, learning, and loving the neighbor to borrowing and spending, using technology, and working in a flexible economy. Along the way, they consider the moral and methodological questions that emerge from this interdisciplinary dialogue and assess the implications for the future of moral theology.